Anti-myopia spectacles: the standard of care in the future? - Lança, Carla (2024)
Reports of myopia increases across the world show an expanding growing public health problem. Myopia prevalence is exceptionally high in some continents, especially in Asia and particularly east Asian countries, but was also reported to have increased in other continents, such as North America and Europe, although there is considerable variation between geographic areas and racial groups in the myopia burden. The presence of myopia, especially high myopia, increases the risk of development of pathologic myopia and visual impairment. The peak incidence of myopia occurs in childhood, but the associated blinding ocular complications develop later during adulthood. Children with an increased risk of visual impairment due to pathologic myopia often have a longer duration of the disease, longer axial length (AL), and thinner choroid. Thus, myopia control therapies should be implemented early to avoid the development of high myopia, as the early age of myopia onset plays a fundamental role in myopia progression, with about 50% of children with myopia onset at 7 or 8 years of age developing high myopia in adulthood, if left untreated. Increased prevalence of high myopia related to AL elongation is likely to result in higher rates of myopic macular degeneration (MMD). At present, we do not know if treating myopic progression will avoid the development of MMD. However, it seems logical to slow AL elongation to prevent severe disease and complications associated with pathologic myopia. Consequently, controlling myopia progression has become one of the highest priorities for eye care professionals all over the world.